2022
DOI: 10.1177/20552076221084461
|View full text |Cite
|
Sign up to set email alerts
|

The Ava bracelet for collection of fertility and pregnancy data in free-living conditions: An exploratory validity and acceptability study

Abstract: Objective To evaluate the validity and acceptability of the Ava bracelet for collecting heart rate, sleep, mood, and physical activity data among reproductive-aged women (pregnant and nonpregnant) under free-living conditions. Methods Thirty-three participants wore the Ava bracelet on their non-dominant wrist and reported mood and physical activity in the Ava mobile application for seven nights. Criterion validity was determined by comparing the Ava bracelet heart rate and sleep duration measures to criterion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 51 publications
(75 reference statements)
0
11
0
Order By: Relevance
“…Twenty-one studies described the application of wearable sensors to collect information about maternal parameters and activities during pregnancy [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. These studies are described in Table 2 , together with a summary of the design and population, wearable device used, and main findings.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Twenty-one studies described the application of wearable sensors to collect information about maternal parameters and activities during pregnancy [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. These studies are described in Table 2 , together with a summary of the design and population, wearable device used, and main findings.…”
Section: Resultsmentioning
confidence: 99%
“…Controversies, however, existed principally around the feasibility of applying them in studies involving pregnant women. For instance, Nulty and colleagues explored the validity and acceptability of a commercially available activity tracker in pregnant and non-pregnant women [ 35 ]. Preliminary analyses conducted by the authors suggested that data collected through the activity tracker did not correlate well with criterion measures.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations